Refugee, Shelter and Threat: Nature Represented in f. Sionil Jose’s Dusk - Kristiawan Indriyanto (Lire Journal (Journal of Linguistics and Literature), 2017)
This paper seeks to explore the role and representation of nature in F.Sionil Jose’s Dusk. He explores the journey of a Philippines’ clan who migrates from Northern Luzon into Central Plains to escape the Spanish oppression. Through the presentation of an omniscient narrator who narrates the journey of Istak Samson and his clan, F.Sionil Jose depicts the lushness of Philippines’ wilderness. To explore his representation of nature, this paper applies narratology and ecocriticism. Several narratological concepts used are mainly related with the issue of space, concerning the presentation and the spatial standpoint of the depiction of nature. These concepts analyze how the omniscient narrator of Dusk portrays the wilderness of Philippines interior. Nature is primarily depicted in two aspects. Firstly, nature can provide shelter, nourishment, and also comfort for the humanity. Secondly, nature is also an untamed and even hostile force who can claim the life of people who pass through it.